(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes paradigmatic relations in symbols expressed by lexical means of the Uzbek language. In particular, the phenomena of synonymy, antonymy, polysemy, polyfunctionality of symbols were studied and their uniqueness was substantiated.